2022
DOI: 10.3389/fpubh.2022.925901
|View full text |Cite
|
Sign up to set email alerts
|

Gray wolf optimization-extreme learning machine approach for diabetic retinopathy detection

Abstract: Many works have employed Machine Learning (ML) techniques in the detection of Diabetic Retinopathy (DR), a disease that affects the human eye. However, the accuracy of most DR detection methods still need improvement. Gray Wolf Optimization-Extreme Learning Machine (GWO-ELM) is one of the most popular ML algorithms, and can be considered as an accurate algorithm in the process of classification, but has not been used in solving DR detection. Therefore, this work aims to apply the GWO-ELM classifier and employ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 63 publications
(76 reference statements)
0
8
0
Order By: Relevance
“…The concept of Opposite‐Based Learning (OBL) was originally introduced in the year 2005 (Arora et al, 2022) and has since gained widespread recognition as an effective technique within swarm‐based approaches. OBL facilitates a balanced combination of core trends and enhanced exploration tendencies (Albadr, Ayob, et al, 2022). The fundamental idea behind OBL revolves around generating opposite points based on the initial data points and subsequently seeking improved positions with superior fitness values compared to the original points.…”
Section: Framework Of the Proposed Mhho‐elm Algorithmmentioning
confidence: 99%
See 1 more Smart Citation
“…The concept of Opposite‐Based Learning (OBL) was originally introduced in the year 2005 (Arora et al, 2022) and has since gained widespread recognition as an effective technique within swarm‐based approaches. OBL facilitates a balanced combination of core trends and enhanced exploration tendencies (Albadr, Ayob, et al, 2022). The fundamental idea behind OBL revolves around generating opposite points based on the initial data points and subsequently seeking improved positions with superior fitness values compared to the original points.…”
Section: Framework Of the Proposed Mhho‐elm Algorithmmentioning
confidence: 99%
“…As mentioned above, researchers also employ notable evolutionary algorithms such as particle swarm optimization (PSO) (Albadr & Tiun, 2020; Zhu et al, 2020), genetic algorithm (GA) (Albadr et al, 2019; Albadr, Tiun, Ayob, Al‐Dhief, Omar, & Hamzah, 2020; Yang et al, 2013), differential evolution (DE) (Li et al, 2020), competitive swarm optimizer (CSO) (Eshtay et al, 2020), Gray wolf optimizer (GWO) (Albadr, Ayob, et al, 2022) and salp swarm algorithm (SSA) (Yaseen et al, 2020) techniques to improve the performance of the ELM neural network models. In several works that utilized the integration of evolutionary swarm intelligence algorithms with ELM network, the authors showed the excellent outcome of their hybrid algorithms by benchmarking the state of the art datasets.…”
Section: Introductionmentioning
confidence: 99%
“…The matrix of the output weights 𝐖 ̂= [W 𝑜𝑖 W 𝑜ℎ ] can be determined via the inverse of the Moore-Penrose generalization as shown in (5).…”
Section: Classification: Fln Algorithmmentioning
confidence: 99%
“…Machine learning (ML) and deep learning (DL) algorithms have been extensively applied due to such algorithms have proved their effectiveness and efficiency in the classification between subjects [4]. Moreover, the algorithms of ML and DL have improved the performance of many recent systems and in different fields such as images classification in the medical domain [5]- [7], language identification [8], [9], fog-cloud network [10], identification of spam emails [11], speech emotion recognition [12], vehicle detection [13] and voice pathology detection [14]- [16]. Additionally, the algorithms of DL and ML have been implemented as the main role in the methods of facial emotion recognition [17], [18].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, ML techniques have been used in many medical applications such as COVID-19 detection [18]; lung cancer detection [19]; voice pathology classification [20]; breast cancer detection [21]; and diabetes disease detection [22,23]. One of the most dangerous illnesses facing the world recently is COVID-19 [24].…”
Section: Introductionmentioning
confidence: 99%